2012
DOI: 10.2214/ajr.11.7442
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Incomplete Atypical Femoral Fractures in Asymptomatic Patients on Long-Term Bisphosphonate Therapy

Abstract: The 2% frequency of incomplete atypical femoral fractures in asymptomatic patients on long-term bisphosphonate therapy is higher than suggested in the literature. Aside from age and mean iPTH, there were no significant differences in clinical or laboratory data between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…One study found that two bisphosphonate users out of 100 studied prospectively had radiographic evidence of impending fracture such as beaking of the femoral cortex [3]. …”
Section: Introductionmentioning
confidence: 99%
“…One study found that two bisphosphonate users out of 100 studied prospectively had radiographic evidence of impending fracture such as beaking of the femoral cortex [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that 7/9 (78%) incomplete AFFs were not associated with a discernable fracture line in the bump on lateral femoral cortex. Such incomplete AFFs can be easily confirmed by a positive isotope bone scan or an MRI [12, 14, 32]. In a study of Koh et al [20], all 4 patients with complete AFF had a fracture line across the thickened cortex seen in pre-AFF radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete AFF is characterized by cortical thickening associated with a beaking or bump at the lateral cortex of the femur, in which a transverse fracture line is often visible [8]. However, several recent reports indicate that fracture line is not always seen in the bumps at lateral cortex of the femur [914]. Complete AFF, progressing from an incomplete fracture, extends through both cortices and usually has a medial spike, the fracture is in transverse or short-oblique orientation, and mostly not comminuted [8].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term use can lead to quantitatively harder osseous matrix, but one that is inherently more brittle and less resilient to microtrauma, resulting in osteonecrosis of the jaw or atypical femoral subtrochanteric insufficiency fractures [36][37][38]. The incidence of atypical femoral subtrochanteric fractures in patients on bisphosphonate therapy for more than 3 years may be as high as 2 % [39,40]. These may be bilateral in up to 55 % of cases [41].…”
Section: Bisphosphonate-related Atypical Subtrochanteric Femoral Fracmentioning
confidence: 99%
“…Once a bisphosphonate-related atypical insufficiency fracture is recognized, conservative measures such as limited weightbearing and serial radiographs are performed [39]. In addition, radiographs of the opposite femur should be obtained, as these can be bilateral in up to 55 % of cases [41].…”
Section: Bisphosphonate-related Atypical Subtrochanteric Femoral Fracmentioning
confidence: 99%